ART BOOKS IN CONTEMPORARY CULTURAL SPACE - Strode, Aina; Līpenīte-Čudarāne, Gita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
A study on art books is necessary to understand their role in contemporary cultural spaces and how to create a great book on art that contributes to enriching cultural landscapes. The article highlights the relevance of printed books in today's context, focusing on art themes, emphasizing the significance of art literature in the digital age, pointing out its ability to offer a deeper engagement with art phenomena. The aim of the article is to explore the types of art books and their significance in contemporary cultural spaces. Research methods include theoretical approaches involving the exploration, compilation, and analysis of relevant scientific and professional literature and sources. A survey, conducted through structured interviews, involved questioning cultural and art experts about the significance of art books in today's cultural spaces. The results of the study demonstrate that the relevance of books, including art books, will persist; their publication in print format will not disappear as art books possess added value created by the physical, tangible format of the book, its design elements, material properties, and diverse culturally significant content.